Human Quiz – Uma Proposta de Jogo Educativo e Informativo dos Direitos Transindividuais: Direitos da Criança e do Adolescente, Direitos da Mulher, Direitos do Idoso e Direitos do Consumidor - Silva, Allan L. da; Cordeiro, José J. R. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
An efficient strategy to disseminate knowledge of playful and fun way is through digital games. In this scenario, educational games are interesting for help in learning why simulate real situations. In this article, we present the Human-game Quiz, which was designed to assist the learning of concepts related the transindividuais rights. The Human-Quiz is a 2D game, multi-phase, multi-platform, aimed at the general public, which will provide a stimulating learning environment.